Knowledge on birth control methods among married males and females in a rural community - Calaguing, Mary Jean C. (1998.)
This is a study on the knowledge of birth control methods among married males and females in a rural community. The study sought to 1) describe the overall knowledge of married males and females regarding birth control methods; 2) know the common birth control method known and used by married males and females; 3) know the different sources of knowledge on birth control methods and 4) to find out if there is a relationship between awareness and use of birth control methods. The study was conducted in Bgy. Buga, Leon. The respondents of the study are 45 married males and 45 married females. The instrument used was the interview schedule. The hypothesis was analyzed using the Linear Regression Test Based on the findings, it was concluded that for married males and females in Bgy. Buga, Leon, the females are more aware of the different kinds of birth control methods and its proper use. The common birth control known by most females is the pill and it is also the most used method. For the males the common birth control method known is the condom, while the most practiced method is the rythm or calendar method. The primary source of knowledge or information on birth control methods is the barangay health center. Knowledge is an important factor in determining the use of birth control methods, however there are some factors that may affect the use of birth control methods. The study found out that there is no significant relationship between awareness of birth control methods and use of birth control methods.
Thesis (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Birth Control Methods -- Knowledge -- Rural Community; Males, Married -- Birth Control Methods